Approximation Solutions for System of Linear Fredhom Integral Equations by Using Decomposition Method - H. S. Ali; W. S. Ali; N. M. Rahmah (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
In this paper, the Decomposition method was used to find approximation solutions for a system of linear Fredholm integral equations of the second kind. In this method the solution of a functional equations is considered as the sum of an infinite series usually converging to the solution, and Adomian decomposition method for solving linear and nonlinear integral equations. Finally, numerical examples are prepared to illustrate these considerations.